Nationwide potential groundwater recharge trends in Bolivia: a remote sensing approach and a policy-ready decline indicator - Mónica Guzmán-Rojo; César Pérez-Hurtado; Zorel Gómez-Vargas (Environmental Research Letters, 2025)
Groundwater provides global water security, supplying over half of the world’s drinking water. In Bolivia, it is particularly important for mitigating drought impacts and sustaining municipal supply. Yet national planning still lacks a clear picture of how groundwater recharge is changing. This study maps potential groundwater recharge change for all 338 municipalities from 1983 to 2022 and presents a policy-oriented risk indicator. Monthly precipitation (P), evapotranspiration (ET), and runoff (R) were obtained from TerraClimate (≈4 km) and FLDAS (≈10 km). A water-balance model converted these variables to potential groundwater recharge. Mann–Kendall and Theil–Sen statistics quantified long-term trends, and Pettitt’s test located years of abrupt change. The Annual Reduction of Potential Groundwater Recharge (RAPReHS) was derived to classify each municipality into one of five risk levels based on long-term groundwater recharge trends. Negative trends are significant in 65% of municipalities, and 71% record at least one breakpoint, most often between 2012 and 2015. Santa Cruz shows the steepest mean decline (–1.9 mm yr ^−1 ), yet similar losses occur along the Chapare–Yungas corridor of La Paz and Cochabamba, the southern lowlands of Beni, and the Chaco of Tarija. By contrast, Pando and parts of northern Beni retain near-neutral or slightly positive slopes, highlighting strong hydro-climatic heterogeneity. Spatial comparison between RAPReHS results and, deforestation and fire statistics reveals strong alignment. Municipalities in the ‘high’ and ‘severe’ classes spatially overlap with the main zones of primary forest loss recorded in Bolivia between 2000 and 2022. The RAPReHS framework, therefore, provides a reproducible, policy-ready lens through which to track groundwater as land-use pressures and climate variability intensify.